The Essence of Coaching Tools That Determine Managerial Skills - Miroslaw BETKOWSKI (Communications of International Proceedings, 2023)
Coaching has become a popular tool to aid professional development, especially for managers who often face numerous challenges and pressures in the workplace. By helping to identify and develop leadership, stress management and self-development skills, coaching can contribute to the success of managers and the organization as a whole. Evaluation of the coaching process is a key element to assess its effectiveness and impact on managers' professional development. Coaching is a dynamic and constant-changing environment, therefore literature is not sufficient in order to cover this topic, in particular coherent and comprehensive analysis of the behaviour of people involved in the coaching based on surveys. Author used scientific methodology, in particular comparatitive methodology and descriptive methodology which is strenghtened with empiric approach based on surveys. The main findings of the article is thatm anagers who are aware of their strengths and are able to use them in their work achieve better results. Coaching in this situation is the optimal tool to help managers identify their strengths and apply them to their daily tasks. Moreover, managers should have in their arsenal is the SMART model necessary for identifying and formulating goals, where active listening is another important factor in supporting a manager's work. On ot the findings in this article is that managers need to be effective leaders who can build trust, support the development of their employees and maintain strong relationships. Coaching can help managers develop these skills by providing support, recognition and constructive feedback to team members.
Keywords: Coaching Tools; Management; Skills